Analytical Computation of Information Rate for MIMO Channels - Jinbao Zhang; Zhenhui Tan; Song Chen (Journal of Computer Networks and Communications)
Information rate for discrete signaling constellations is significant. However, the computational complexity makes information rate rather difficult to analyze for arbitrary fading multiple-input multiple-output (MIMO) channels. An analytical method is proposed to compute information rate, which is characterized by considerable accuracy, reasonable complexity, and concise representation. These features will improve accuracy for performance analysis with criterion of information rate.